2007
DOI: 10.1371/journal.pone.0001016
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Receptor CXCR4 Strongly Promotes Neuroblastoma Primary Tumour and Metastatic Growth, but not Invasion

Abstract: Neuroblastoma (NB) is a heterogeneous, and particularly malignant childhood neoplasm in its higher stages, with a propensity to form metastasis in selected organs, in particular liver and bone marrow, and for which there is still no efficient treatment available beyond surgery. Recent evidence indicates that the CXCR4/CXCL12 chemokine/receptor axis may be involved in promoting NB invasion and metastasis. In this study, we explored the potential role of CXCR4 in the malignant behaviour of NB, using a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 36 publications
7
56
2
1
Order By: Relevance
“…Surface expression of CXCR4 has been shown to be low in several neuroblastoma cell lines (Carlisle et al, 2009). Nevertheless, CXCR4 overexpression is an indicator of worse outcomes for patients with neuroblastoma (Russell et al, 2004) and is also associated with site-specific metastasis particularly to the bone marrow (Geminder et al, 2001;Meier et al, 2007;Ben-Baruch, 2009). To mimic neuroblastoma with elevated CXCR4, and to facilitate our structure/function studies of CXCR4 downregulation, we overexpressed CXCR4 in SH-SY5Y cells using transient transfection of an expression plasmid encoding wild-type CXCR4 tagged with fluorescent YFP (CXCR4wt).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface expression of CXCR4 has been shown to be low in several neuroblastoma cell lines (Carlisle et al, 2009). Nevertheless, CXCR4 overexpression is an indicator of worse outcomes for patients with neuroblastoma (Russell et al, 2004) and is also associated with site-specific metastasis particularly to the bone marrow (Geminder et al, 2001;Meier et al, 2007;Ben-Baruch, 2009). To mimic neuroblastoma with elevated CXCR4, and to facilitate our structure/function studies of CXCR4 downregulation, we overexpressed CXCR4 in SH-SY5Y cells using transient transfection of an expression plasmid encoding wild-type CXCR4 tagged with fluorescent YFP (CXCR4wt).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to MYCN gene amplification, DNA ploidy changes, and expression of neurotrophin receptors (Vasudevan et al, 2005;Raffaghello et al, 2009;Huang et al, 2011;Davidoff, 2012), elevated expression of the CXCR4 CXC chemokine receptor is a marker and proposed drug target for high-risk neuroblastoma (Shim et al, 2009). CXCR4 expression is associated with neuroblastoma metastatic growth (Liberman et al, 2012), clinical presentation in bone marrow and liver (Geminder et al, 2001;Russell et al, 2004;Meier et al, 2007;Raffaghello et al, 2009;Zhao et al, 2012), and poor prognosis (Russell et al, 2004). Unfortunately, pharmacological targeting of CXCR4 is complicated by the widespread expression of CXCR4 on normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The CXCL12/CXCR4 axis is involved in several aspects of tumor progression including angiogenesis, metastasis, and survival (1,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The bone marrow microenvironment facilitates the survival, differentiation, and proliferation of normal hematopoietic cells, malignant hematopoietic cells, and epithelial tumor cell bone metastasis.…”
Section: Cxcr4 and Cancermentioning
confidence: 99%
“…Moreover, chemokines play a major role in tumor growth, angiogenesis, and invasion (10,11) in several cancers and neoplastic cells may express chemokine receptors (12). Over the last years, CCR1, CCR5, CCR6, CCR9, CXCR1, CXCR2, CXCR4, CXCR5, and CXCR6 were found expressed in neuroblastoma and it has been shown that CXCR4 is virtually expressed in all human neuroblastoma cell lines (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%